Polymeric Microneedle Arrays: Versatile Tools for an Innovative Approach to Drug Administration. Issue 8 (6th June 2019) - Dardano, Principia; Battisti, Mario; Rea, Ilaria; Serpico, Luigia; Terracciano, Monica; Cammarano, Aniello; Nicolais, Luigi; De Stefano, Luca
Abstract: Mainly designed and realized as a painless alternative to the hypodermic syringe, microneedle‐based devices are currently approaching commercial market placement. The considerable academic and industrial investment in this technology is reflected by a multitude of papers published and patents registered every year, which is also a sign of a field in full fermentation. New materials and innovative methodologies are continuously exploited in search of the best performance at the lowest cost. For these reasons, an updated review, focused predominantly on the last year of scientific production, is a useful guideline in this rapidly changing panorama. This report provides a critical review of microneedle technologies presented in the very recent literature with a particular focus on those closest to the needs of the healthcare field. Although a few devices are already commercial, further effort is still needed to achieve complete clinical translation and therapeutic efficacy competitive with or superior to those of the devices used as standards and adopted by national health systems. Abstract : Microneedle technology can be adopted for the effective, controlled, and painless delivery of drugs and, in general, testing of active molecules. This innovative technological platform can revolutionize the administration of therapies and improve healthcare management.